Liquid-liquid phase separation of germline proteins - Babl, L (2019)
Spatial organization of chemical processes is a widely accepted requirement for living systems. Cells have developed a great variety of mechanisms to achieve spatial and temporal organization of which many rely on lipid membranes to separate biochemical processes from bulk phases. However, studies in recent years have shown that membraneless organelles are highly dynamic entities that can organize and facilitate chemical reactions. Membraneless organelles are known to consist of a diverse population of different proteins and nucleic acids. Many studies focus on the phase behaviour and properties of single protein regions. We therefore investigated the phase behaviour of more complex systems using the well-characterized germ granule protein Ddx4 and the uncharacterized N-terminal regions of Piwi proteins. We show that the interplay of these disordered regions has differential effects on the phase properties and the propensity to phase separate. Furthermore, we find that liquidliquid phase separation of Piwi protein N-terminal regions is dependent on folded domains. The evolution of disordered proteins is not well understood and experimental data is scarce. Therefore, we compared the phase behaviour of human germ granule proteins to Drosophila melanogaster proteins. We show that the propensity to phase separate, phase properties and interactions of composite systems are evolutionarily conserved between Homo sapiens and Drosophila melanogaster homologues, even though sequence similarity is remarkably low.